2012
DOI: 10.1063/1.4729948
|View full text |Cite
|
Sign up to set email alerts
|

The I2 dissociation mechanisms in the chemical oxygen-iodine laser revisited

Abstract: The recently suggested mechanism of I(2) dissociation in the chemical oxygen-iodine laser (COIL) [K. Waichman, B. D. Barmashenko, and S. Rosenwaks, J. Appl. Phys. 106, 063108 (2009); and J. Chem. Phys. 133, 084301 (2010)] was largely based on the suggestion of V. N. Azyazov, S. Yu. Pichugin, and M. C. Heaven [J. Chem. Phys. 130, 104306 (2009)] that the vibrational population of O(2)(a) produced in the chemical generator is high enough to play an essential role in the dissociation. The results of model calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This is much less than the value of 7.5 × 10 –15 cm 3 s –1 proposed for the first reaction to explain dthe issociation rate via this cascade mechanism . For the cascade mechanism where I 2 * = I 2 ( 3 Π 2u ), it was suggested that I 2 ( 3 Π 2u ) can be produced much more efficiently in collisions of I 2 with O 2 (a, v ≥ 1), which can be formed in reaction . , Excited molecules I 2 ( 3 Π 2u ), O 2 (a, v ≥ 1), and I 2 (X, v > 20) play an important role in COIL modeling as intermediates in the initiation and chain stages of iodine dissociation. ,, …”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…This is much less than the value of 7.5 × 10 –15 cm 3 s –1 proposed for the first reaction to explain dthe issociation rate via this cascade mechanism . For the cascade mechanism where I 2 * = I 2 ( 3 Π 2u ), it was suggested that I 2 ( 3 Π 2u ) can be produced much more efficiently in collisions of I 2 with O 2 (a, v ≥ 1), which can be formed in reaction . , Excited molecules I 2 ( 3 Π 2u ), O 2 (a, v ≥ 1), and I 2 (X, v > 20) play an important role in COIL modeling as intermediates in the initiation and chain stages of iodine dissociation. ,, …”
Section: Introductionmentioning
confidence: 89%
“…10,12−15 Excited molecules I 2 ( 3 Π 2u ), O 2 (a,v ≥ 1), and I 2 (X,v > 20) play an important role in COIL modeling as intermediates in the initiation and chain stages of iodine dissociation. 12,14,15 Experiments performed in refs 9, 10, and 13 were done at high initial concentrations of molecular iodine. Under these conditions, the contribution of the initiating stage into the total dissociation rate was very small compared to the chain stage.…”
Section: Introductionmentioning
confidence: 99%